3D Geometry Learning Using GeoGebra on Students' Mathematical Reasoning Ability - Loliyana; Jody Setya Hermawan; Anisa; Ika Wulandari Utamining Tias; Fatkhur Rohman; Amrina Izzatika; Syarifatul Muafifah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Along with the development of sophisticated science and technology (IPTEK), the tools used by educators are not optimal in learning. This can be seen from the lack of student interaction during learning activities. Students do not have the opportunity to use the media that are used by educators frequently. In geometry learning on the material of building space, the understanding level of students on this material requires visualization. Students are confused about imagining the shape of the building space. Hence, the research method used by the researcher is descriptive research with a quantitative approach, which describes a situation objectively using numbers ranging from data collection, data interpretation and appearance, as well as the results. Based on the research result that has been conducted, there is an effect of the implementation of GeoGebra on 3D geometry learning space building material on the mathematical reasoning ability. In addition, the effect of GeoGebra implementation on learning geometry 3D space building material on mathematical reasoning ability is 94.9%.